Fundamental and Applicative Aspects of the Unfolded Protein Response in Yeasts - Yuki Ishiwata-Kimata; Yukio Kimata (Journal of Fungi, 2023)
Upon the dysfunction or functional shortage of the endoplasmic reticulum (ER), namely, ER stress, eukaryotic cells commonly provoke a protective gene expression program called the unfolded protein response (UPR). The molecular mechanism of UPR has been uncovered through frontier genetic studies using Saccharomyces cerevisiae as a model organism. Ire1 is an ER-located transmembrane protein that directly senses ER stress and is activated as an RNase. During ER stress, Ire1 promotes the splicing of HAC1 mRNA, which is then translated into a transcription factor that induces the expression of various genes, including those encoding ER-located molecular chaperones and protein modification enzymes. While this mainstream intracellular UPR signaling pathway was elucidated in the 1990s, new intriguing insights have been gained up to now. For instance, various additional factors allow UPR evocation strictly in response to ER stress. The UPR machineries in other yeasts and fungi, including pathogenic species, are another important research topic. Moreover, industrially beneficial yeast strains carrying an enforced and enlarged ER have been produced through the artificial and constitutive induction of the UPR. In this article, we review canonical and up-to-date insights concerning the yeast UPR, mainly from the viewpoint of the functions and regulation of Ire1 and HAC1.